Phytochemicals reduced growth, sporulation and conidial dimensions of Fusarium verticillioides, cause of fumonisin contamination in maize grains - Habtamu Terefe; Getnet Yitayih; Getachew G. Mengesha (Biotechnology Reports, 2023)
The objective of the study was to evaluate the effectiveness of methanolic extracts of plants against radial growth and spore dimensions of Fusarium verticillioides. Leaf extracts of 25 plants were tested against the fungus. Of which, thirteen extracts were potent against the fungus and evaluated using food poising technique. Growth was evaluated on PDA medium amended with the extracts at 5 mg ml–1. Control treatments included plates without (negative) extracts and with synthetic (positive) fungicide. Spore dimension was determined using PDB. The results showed T. vulgaris extract completely inhibited mycelial growth of the fungus as equivalent as the fungicide. Similarly, G. parviflora, C. citratus, R. officinalis, R. chalepensis, and Agave sp. also recorded growth reductions ranging from 71.04 to 81.35 % at day seven. In addition, extracts of Agave sp., C. citratus and T. vulgaris did not support sporulation. Overall, the results indicate that T. vulgaris extracts could be safe source of bioactive chemicals to control F. verticillioides.